Assessment of cultural beliefs and practices during the postnatal period in an urban field practice area of SRMC, Nandyal, Kurnool, Andhra Pradesh - Venkateswarlu, M.; Pasha, M. A. Mushtaq; Fatima, Afsar (International Journal Of Community Medicine And Public Health, 2019)
Background: The postpartum period continues to be an important part of the tradition and culture among Indian women. But frequently the health of the postnatal women is neglected. So, the present study aimed to explore the beliefs and practices in the postpartum period regarding diet, rest, hygiene, confinement and assess association between cultural practices and socio demographic characteristics. Methods: A cross‐sectional descriptive study was conducted in the field practice area of urban SRMC Nandyal. The participants were women who had given births in the past three months. The data was collected using a pre‐tested semi‐structured questionnaire. Results: Among the 140 women, over 75% of women had increased their diet intake postpartum. Vegetables such as brinjal and fruits like papaya were avoided by 58.5% and 63.6% women respectively. Among the mothers 18.3% consumed less than 500 ml of water every day and 22% did not drink milk at all. Household work was avoided by 67% of the women while 79.6% avoided going outdoors. Many women didn’t maintain personal hygiene. Many women took home remedies for faster recuperation. These practices were influenced by the socioeconomic status and the woman’s educational status. Conclusions: Traditional postpartum practices are still popular among women in rural and slum areas in Andhra Pradesh. It is critical to identify the harmful practices and reinforce the positive healthy practices to make postpartum period a healthy and joyful period for the mother.